Usability Testing of an Academic Library Website: A Study of Student Navigation Behaviours With AI-Assisted Data Analysis - Wegener, Debby R.; Chew, Yu Ying (Evidence Based Library and Information Practice, 2026)
Objective – This study investigated the search strategies and navigation behaviours of students on an academic library website, with the focus being on identifying usability challenges and opportunities for improvement. The researchers also wanted to test the effectiveness of generative artificial intelligence (GenAI) in analysing qualitative usability data.Methods – A mixed-methods usability study was conducted with 21 second-year university students. Participants completed three task scenarios on the library website while their screen activity and think-aloud comments were recorded. Quantitative data was collected using a modified usability questionnaire, and the qualitative data was analyzed using multiple GenAI platforms following established prompt frameworks, with human review for accuracy.Results – Students encountered significant barriers in navigation, layout, content accessibility, and functionality. Many preferred external tools like Google over the library website, citing complexity and difficulty in locating resources. The average usability questionnaire score was 50 out of 100, with higher scores among students who had attended library training. GenAI tools expedited qualitative analysis but required careful prompt engineering and human oversight to ensure accuracy and context relevance.Conclusion – The findings highlight the need for ongoing, user-centered design improvements to library websites, emphasizing clear navigation, accessible content, and reduced complexity. Regular usability testing and integration of user feedback are recommended to enhance digital library services. In addition, while GenAI can accelerate qualitative analysis, human expertise currently remains essential for nuanced interpretation and validation.